The Development of Super-Saturated Rebamipide Eye Drops for Enhanced Solubility, Stability, Patient Compliance, and Bioavailability - Dong-Jin Jang; Jun Hak Lee; Da Hun Kim; Jin-Woo Kim; Tae-Sung Koo; Kwan Hyung Cho (MDPI AG, 2023)
The present study aimed to develop clear aqueous rebamipide (REB) eye drops to enhance solubility, stability, patient compliance, and bioavailability. For the preparation of a super-saturated 1.5% REB solution, the pH-modification method using NaOH and a hydrophilic polymer was employed. Low-viscosity hydroxypropyl methylcellulose (HPMC 4.5cp) was selected and worked efficiently to suppress REB precipitation at 40 °C for 16 days. The additionally optimized eye drops formulation (F18 and F19) using aminocaproic acid and D-sorbitol as a buffering agent and an osmotic agent, respectively, demonstrated long-term physicochemical stability at 25 °C and 40 °C for 6 months. The hypotonicity (<230 mOsm) for F18 and F19 noticeably extended the stable period, since the pressure causing the REB precipitation was relieved compared to the isotonic. In the rat study, the optimized REB eye drops showed significantly long-lasting pharmacokinetic results, suggesting the possibility of reducing daily administration times and increasing patient compliance (0.50- and 0.83-times lower Cmax and 2.60- and 3.64-times higher exposure in the cornea and aqueous humor). In conclusion, the formulations suggested in the present study are promising candidates and offer enhanced solubility, stability, patient compliance, and bioavailability.